Multi-locational assessment of some physicochemical attributes and amylase activity of sweetpotato varieties and elite materials in Ghana. - Owusu-Mensah, E.; Oduro, I.; Asafu-Agyei, J.N.; Adofo, K.; Obeng-Bio, E.; Asamoah-Obeng, N.; Awoodzie, J.K.; Carey, E.E. (2012)
As part of the breeding objectives to select sweetpotato materials with acceptable quality attributes for adaptation and subsequent utilisation in Ghana, the total amylase activity and physicochemical attributes (flesh colour, Beta-carotene, dry matter, starch and sugars) of 13 sweetpotato genotypes across five locations were evaluated. Near Infrared Reflectance Spectrometry (NIRS), was mainly employed in the study. The flesh colour of the materials ranged from white to deep orange while thedry matter content ranged from 20% to 44%. Starch, fructose, glucose and sucrose contents were 46– 74, 0.3 - 5, 2 – 8 and 9 – 22% respectively. Apomuden, a deep orange type, recorded the highesttotal sugar content of 36% and the lowest dry matter and starch content of 20% and 46% respectively. Hi-starch variety had the highest dry matter (45%), starch (74%) and the lowest sugar (11%). Dry matter content correlated positively with starch content whilst orange colour intensity was inversely proportional to dry matter content. The outcome of the study supports the fact that sweet potato contains high extractable amylases. Amylase activity of the materials was fairly stable across locations. Okomkum, Faara, Santom Pona, Kemb, and Cemsa 74-228 recorded the highest activity while Hi-starch, Apomuden, Mohc, and 199062.1 were low. There was no correlation between raw sugars and amylase activity. The potential of individual cultivars for food industry will be discussed in relation to starch content and extractable amylases.